An Potential Energy Surface for the $O+O_2$ Reaction Using Neural Network Approach (Journal of Atomic and Molecular Sciences, 2019)
A new potential energy surface (PES) of the $O_3$ system was reported, based on the PESs reportedby Dawes et al. and Schinke et al. The PES of $O_3$ reported by Dawes et al. was fitted using least squaremethod based upon accurate high level ab initio points, and has been applied to many dynamics calculations.However, it is computationally slow and need lots of time to obtain the energy points from the PES. At thesame time, the threshold of the ab initio points is low as 2.6 eV, relative to the minimum of the PES, whichlimits its application. On the contrary, the PES reported by Schinke et al. numerically is fast and extends tohigh energy. In this work, we first calculated the energy points from these two PESs. Then we fitted theseenergy points using PIP-NN approach. In this way, a revised version of the PES of $O_3$ was constructed and weused it to perform quantum reactive scattering dynamics calculation.